The Arts of Coexistence: A View From Anthropology - Schroer, Sara Asu (Frontiers in Conservation Science, 2021)
In this perspectives essay, I propose some ways in which current thinking in anthropology might inform the emergent cross-disciplinary field of coexistence studies1. I do so following recent calls from within the conservation science community (including this special issue), acknowledging that understanding human-wildlife coexistence in the fractured landscapes of the Anthropocene2 requires being open to alternative approaches beyond conventional frameworks of conservation science and management (see for instance; Carter and Linnell, 2016; Pooley, 2016; Chapron and López-Bao, 2019; Pooley et al., 2020). The essay suggests that relational (non-dualist) ways of thinking3 in anthropology, often building on Indigenous philosophy and expertise, may help ground coexistence studies beyond Euro-Western modernist conceptual frameworks—frameworks that perpetuate exploitative and colonial logics that many scholars from across academia view as being at the heart of our current ecological crisis (e.g., Lestel, 2013; van Dooren, 2014; Tsing, 2015; Todd, 2016; Bluwstein et al., 2021; Schroer et al., 2021). By proposing “relations” rather than objectified “Nature” or “wildlife” as the more adequate subject of understanding and facilitating coexistence in shared landscapes, I understand coexistence and its study first and foremost as an ethical and political endeavor. Rather than offering any conclusive ideas, the essay's intention is to contribute some questions and thoughts to the developing conversations of coexistence studies scholars and practitioners. It does so by inviting conservation scientists to collaborate with anthropologists and take on board some of the current thinking in the discipline. Amongst other things, I suggest that this will help overcome a somewhat dated notion of cultural relativism—understood as many particular, cultural views on one true objective Nature (only known by Science), a perspective that explicitly and implicitly seems to inform some conservation science approaches to issues of culture or the “human dimensions” of conservation issues. Ultimately, the paper seeks to make a conceptual contribution by imagining coexistence as a dynamic bundle of relations in which the biological, ecological, historical, cultural, and social dimensions cannot be thought apart and have to be studied together.